The Influence of the Register of Non-Tax Revenues on the Efficiency of the Non-Tax Revenue System in the Republic of Croatia - Domagoj Karačić; Ivana Bestvina Bukvić; Mladena Bedeković (Central European Public Administration Review)
Non-tax revenues and parafiscal charges in most cases represent a limiting factor for the business sector and are an additional burden for citizens. In accordance with the recommendations of the European Commission and the Croatian national strategic documents, a rationalisation of the system of non-tax revenues is necessary to achieve a further lessening of the burden of economic subjects and citizens and to foster economic growth. The aim of this paper is to analyse the non-tax revenues in the Republic of Croatia, analyse their role, their impact on the effectiveness of the system of non-tax revenues and contribute to its understanding, as it represents an important segment for strengthening the competitiveness of the Croatian economy. The study is based on a systematic analysis of non-tax revenues in Croatia. For the purposes of comparative analysis, the following forms of literature were taken into account: different national strategic documents of the Republic of Croatia, the European Commission reports, available statistical indicators and relevant foreign and domestic scientific and professional literature dealing with the problem of non-tax revenue. The time scope of the analysis is the period from 2008 to 2016 and the results were compared with the data obtained from other sources. Croatia has made limited progress in the area of non-tax revenues as one of the components required for the removal of macroeconomic imbalances in the economy.